2019
DOI: 10.1016/j.ijpharm.2019.118692
|View full text |Cite
|
Sign up to set email alerts
|

Alginate-chitosan PEC scaffolds: A useful tool for soft tissues cell therapy

Abstract: In this study we evaluate macroporous scaffolds made of alginate-chitosan polyelectrolyte complexes (PEC) as tools to optimire the results of soft tissues oell therapy. Cell therapy using mesenchymal stem cells (MSC) bas become attractive for tissue repair and regeneration in a number of acute and chronic injuries. Unfortunately their low retention and/or survival after injection limit their beneficial effects. A biomaterial-assisted im plantation, providi ng oells a thr�mensional (3D) microenvironment is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 97 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…They can also be used to enhance interactions between therapeutic and host tissues. While PE complexes have been described in cardiac therapeutic applications, it is unknown if they provide extensive benefit over other approaches that are simpler to manufacture, especially when the scale is important [21][22][23] . We were successful in creating similar architecture with our TE scaffold.…”
Section: Comparison Of Our Work With That Of Other Investigatorsmentioning
confidence: 99%
“…They can also be used to enhance interactions between therapeutic and host tissues. While PE complexes have been described in cardiac therapeutic applications, it is unknown if they provide extensive benefit over other approaches that are simpler to manufacture, especially when the scale is important [21][22][23] . We were successful in creating similar architecture with our TE scaffold.…”
Section: Comparison Of Our Work With That Of Other Investigatorsmentioning
confidence: 99%
“…A similar approach was proposed by Ibrahim et al [ 128 ], who prepared erodible sponges with xanthan gum/chitosan, polycarbophil/chitosan and Carbopol ® /chitosan PECs loaded with rosuvastatin, which showed an increase in bone regeneration capacity in mice. Scaffolds can also be used as tools for soft tissue cell therapy, as proposed by Bushkalova et al [ 129 ], who prepared macroporous scaffolds containing chitosan/alginate PECs and demonstrated that their structure and angiogenic potential made them interesting candidates to improve the results of mesenchymal stem cell therapy in soft tissue engineering. Lastly, PECs are also found in the literature as agents for wound dressing.…”
Section: Polyelectrolyte Complexesmentioning
confidence: 99%
“…cells promoted an increase of vascular density constituted of both large-and micro-size vascular structures with normal ECs alignment and epithelialization in the periphery. Bushkalova et al (2019), instead, developed macroporous scaffolds made of alginate-chitosan polyelectrolyte complexes to deliver MSCs in soft tissues. This strategy exploits the association of alginate with a cationic polymer, chitosan, to form a polyelectrolyte complex of opposite charge that can be subsequently freezedried and crosslinked; in this way, chemically unaltered polymers preserve their initial biocompatibility while their rheological properties improve and adapt to the mechanical resistance of soft tissues.…”
Section: Alginate In Support Of Heart Vascularizationmentioning
confidence: 99%